Memaknai Upacara Kematian dalam Bingkai Lokalitas Budaya Indonesia: Studi Kasus Tiga Cerpen Pilihan Kompas - Awla akbar Ilma; Puri Bakthawar (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2020)
Indonesian is a multicultural plural society. Therefore, almost every ethnic group in Indonesia has varied tradition and culture, especially in responding to the phenomenon of obsequies through unique ceremonies and symbols. The research aims to examine how people in several ethnic groups responded to the death event through traditional ceremonies represented by literary works, especially short stories in the 2014-2017 Kompas Selections. Samples to be used in this study are the short story